Best Answer

I'm assuming the equation is: yx + 3y = 6 Now, you aren't going to get one answer for this, but you can factor for either x or y. In terms of y, this is y(x + 3) = 6 or y = 6/(x+3) In terms of x, this is yx = 6 - 3y or x = 6/y - 3 If you graph these, you'll get a y=1/x type function with the vertical asymptote at x=-3

Q: What is y x plus 3y equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x + y = 6 so that -x = y - 6 -x + 3y = -2 that is, y - 6 + 3y = -2 or 4y = 4 or y = 1 and then -x = y - 6 = -5 so that x = 5

Put in this form. Y =mX + c X + 3Y - 6 = 0 X + 3Y = 6 3Y = - X + 6 Y = - (1/3)X + 2 --------------------- slope(m) = - 1/3 ------------------------

2x+3y = 6 2x+3(0) = 6 2x = 6 x = 6/2 x = 3

Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!

Yes and it works out that x = 3 and y = 4

Related questions

x + y = 6 so that -x = y - 6 -x + 3y = -2 that is, y - 6 + 3y = -2 or 4y = 4 or y = 1 and then -x = y - 6 = -5 so that x = 5

The answer is - not are : (5, 1).

-x + 3y = 6 3y = x 6 y = x/3 + 2 So slope = 1/3 and intercept = 2

5x+3y

Put in this form. Y =mX + c X + 3Y - 6 = 0 X + 3Y = 6 3Y = - X + 6 Y = - (1/3)X + 2 --------------------- slope(m) = - 1/3 ------------------------

x-y = 6 -x-3y = 22 -4y = 28 y = -7 So by substituting: x = -1 and y = -7

2x+3y = 6 2x+3(0) = 6 2x = 6 x = 6/2 x = 3

x=-3y=4

4.34684352143

x = 2.15 and y = 3.75

The ordered pair is (-1, -7).

Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!